1991
DOI: 10.2307/4002943
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Seedbed Microsite Characteristics on Grass Seedling Emergence

Abstract: Successful germination and establishment of grass seedlings from surface-sown seeds requires a microsite which provides nde quate soil water and temperature conditions, among other speciesspecific requirements. The microsite where these requirements are met has been termed a "safesite". Safesites may occur naturally as cracks and depressions in the soil surface, gravel, and plant litter, or be prepared by seedbed equipment and livestock trampling. A greenhouse study was conducted to determine the intluence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Other microsite types may inhibit successful seedling establishment. Studies have shown low seedling establishment on bare soil and fine‐textured surfaces (Chambers, MacMahon & Haefner 1991; Winkel, Roundy & Cox 1991; Tsuyuzaki et al . 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Other microsite types may inhibit successful seedling establishment. Studies have shown low seedling establishment on bare soil and fine‐textured surfaces (Chambers, MacMahon & Haefner 1991; Winkel, Roundy & Cox 1991; Tsuyuzaki et al . 1997).…”
Section: Discussionmentioning
confidence: 99%
“…No action could leave burned areas in an undesired ecological condition for years (Newhall et al 2004, Steers and Allen 2010, Knutson et al 2014. Applying seed without any attempt to increase soil-seed contact (either using rangeland drill or roughening approaches) can result in very low germination rates (Winkel et al 1991, Bakker et al 2003. But, post-fire soil disturbance increases risk of accelerated erosion and further loss of existing vegetation unless additional erosion-control measures are implemented to mitigate the destabilizing effects of surface disturbance (Pierson et al 2007, Miller et al 2012.…”
Section: How Then To Decide If Active Rehabilitation Is Needed and Imentioning
confidence: 99%
“…Inhabitants of arid regions have life histories and behaviors that are often tightly coupled to the prevailing conditions for which they are adapted. Xeric plants, for example, have physiological traits that prevent germination until narrow hydric and thermal conditions are met [6,7]. As a result, precipitation strongly affects plant productivity seasonally and annually in arid environments [7,8], which in turn affects herbivore populations [9].…”
Section: Introductionmentioning
confidence: 99%